Instagram sebagai Media Informasi Digital Perpustakaan Universitas Pembangunan Nasional “Veteran” Jakarta - Sinaga, Saidun; Muqsith, Munadhil Abdul; Ayuningtyas, Fitria (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The development of information technology enables libraries to improve the effectiveness and the efficiency of services to users by utilizing social media as a communication tool. UPNVJ Library chose Instagram as a platform because of its popularity and suitability of features with utility. The purpose of this study is to analyze the strategy applied by UPNVJ Library in utilizing Instagram as a communication media to improve services to users. This study uses a descriptive qualitative approach to explore the strategy of UPNVJ Library to use Instagram. The results of the study showed that UPNVJ Library uses Instagram as a communication media by using four pillars of social media strategy, namely communication, collaboration, education, and entertainment when providing information through content. In addition, UPNVJ Library adjusts a good strategic communication to notice the most aspec like caption, hashtag, story, highlight, direct message, comment, and like. The another factor which is related to planning content. However, this research found some obstacles in managing Instagram UPNVJ Library’s, the weakness of staff, the least followers in civitas, the difficulty to find them, and hot to make the captions. So to control this researches to recommended some solution, as a increase the staff, make the formation and the training, promotion and hation and make the riset socialization and make the riset of the another account library Instagram so can make the inspiration for other, the references about them and another interesting and relevant.